A BCN film and preparation method thereof
BCN films were prepared by sol-gel method, and the sol stability was improved by using composite chelating agents, which solved the problem of insufficient stability of BCN films in the prior art, and achieved high-performance and low-cost film preparation.
Patent Information
- Application Number
- CN202411977253.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
In the prior art, when preparing CaBi2Nb2O9 (BCN) film, the sol stability is poor, resulting in defects such as cracking and shedding during the film growth, affecting the overall performance of the film.
BCN films were prepared by sol-gel method, and a precursor solution was formed by mixing niobium hydroxide precipitation, composite chelating agent and water, and then adding bismuth ion and calcium ion solutions to hydrolyze and condensation reaction and aging to form a BCN gel and sintered on the substrate surface to obtain a BCN film.
This method reduces the production cost, reduces film defects, improves the performance and purity of the film, and has a simple process, allowing the composition of the film to be controlled more evenly.
Smart Images

Figure CN119774891A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ferroelectric materials, and in particular relates to a BCN film and a preparation method thereof. Background Art
[0002] With the demand for device miniaturization and integration, ferroelectrics, as a new type of ferroelectric material, have important applications in microelectronics, optoelectronics, micro-electromechanical systems, and other fields due to their excellent ferroelectric, piezoelectric, and pyroelectric properties. Bismuth-layered perovskite-type ferroelectric thin films have great application prospects in high-temperature and high-frequency applications due to their excellent fatigue resistance, low aging rate, and high Curie temperature.
[0003] CaBi2Nb2O9 (BCN) is a very typical bismuth layer perovskite structured ferroelectric. The Curie temperature of CaBi2Nb2O9 thin films can reach as high as 940°C, and they have high fatigue resistance. At present, the main methods for preparing BCN thin films include radio frequency magnetron sputtering, pulsed laser deposition, and sol-gel methods. Radio frequency magnetron sputtering and pulsed laser deposition have high requirements for raw materials and equipment. In order to reduce the preparation cost, the related technology uses the sol-gel method to prepare BCN thin films. However, the resulting sol has poor stability, resulting in defects such as cracking and falling off during the film growth process, thereby affecting the overall performance of the film. Summary of the Invention
[0004] The object of the present invention is to provide a BCN film and a preparation method thereof. The preparation method provided by the present invention has low preparation cost and the obtained BCN film has few defects.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a BCN thin film, comprising the following steps:
[0007] Mixing niobium hydroxide precipitate, a composite chelating agent and water, and dissolving them to obtain a precursor solution; the composite chelating agent includes ethylenediaminetetraacetic acid and tartaric acid;
[0008] adding a bismuth ion solution and a calcium ion solution dropwise to the precursor solution, and sequentially performing hydrolysis condensation reaction and aging to obtain a BCN gel;
[0009] The BCN gel is coated on the surface of a substrate and sintered to obtain the BCN film.
[0010] Preferably, the molar ratio of tartaric acid to ethylenediaminetetraacetic acid is 1:1 to 3;
[0011] The molar ratio of the niobium hydroxide precipitate to the composite chelating agent is 1:6-8.
[0012] Preferably, the dissolving temperature is 70-80°C.
[0013] Preferably, the molar ratio of bismuth ions in the bismuth ion solution to niobium ions in the precursor solution is 1:0.9-1.2;
[0014] The molar ratio of calcium ions in the calcium ion solution to niobium ions in the precursor solution is 1:1.9-2.2.
[0015] Preferably, the method further comprises adding a stabilizer to the precursor solution before the hydrolysis condensation reaction; the stabilizer comprises ethylene glycol.
[0016] Preferably, the dripping rate of the bismuth ion solution and the calcium ion solution is independently less than 3 mL / min;
[0017] The temperature of the hydrolysis condensation reaction is 60-80°C, and the reaction time is 1-3 hours;
[0018] The aging temperature is room temperature and the aging time is 20 to 24 hours.
[0019] Preferably, the substrate comprises indium tin oxide glass or fluorine-doped tin oxide glass;
[0020] The sintering temperature is 650-750° C. and the sintering time is 2-3 hours.
[0021] Preferably, the method for preparing the niobium hydroxide precipitate comprises the following steps:
[0022] mixing niobium pentoxide and hydrofluoric acid and performing double decomposition reaction to obtain a niobium fluoride solution;
[0023] The niobium fluoride solution and the ammonium ion solution are mixed, and precipitation reaction and solid-liquid separation are carried out in sequence to obtain the niobium hydroxide precipitate.
[0024] Preferably, the molar ratio of niobium pentoxide to hydrogen fluoride in hydrofluoric acid is 1:10-15;
[0025] The temperature of the metathesis reaction is 150-180° C., and the reaction time is 2-3 hours.
[0026] The present invention also provides a BCN film prepared by the preparation method described in the above technical solution.
[0027] The present invention provides a method for preparing a BCN thin film, comprising the following steps: mixing a niobium hydroxide precipitate, a composite chelating agent, and water, and dissolving the mixture to obtain a precursor solution; the composite chelating agent comprises ethylenediaminetetraacetic acid and tartaric acid; dropwise adding a bismuth ion solution and a calcium ion solution to the precursor solution, sequentially performing a hydrolysis-condensation reaction and aging to obtain a BCN gel; and coating the BCN gel on a substrate surface and sintering the BCN thin film. The present invention prepares the BCN thin film using a sol-gel method. Compared with other preparation methods, the sol-gel method offers a simpler preparation process, enables a more uniform composition of the film, and produces high-purity films at a lower cost. Furthermore, compared with the single chelating agent commonly used in traditional thin film preparation, the composite chelating agent can form more stable and complex complexes with the metal ions in the sol, which is more conducive to the preparation of a stable sol, reduces film defects, and produces films with superior performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0029] Figure 1 Flow chart of the preparation method of the BCN thin film described in Examples 1 to 6;
[0030] Figure 2 XRD patterns of the BCN films obtained in Examples 1 to 3;
[0031] Figure 3 XRD patterns of the BCN films obtained in Examples 4 to 6;
[0032] Figure 4 The SEM images of the BCN films obtained in Examples 1 to 6, wherein Figures a to f correspond to Examples 1 to 6 respectively;
[0033] Figure 5 Peak analysis diagram of O1s XPS photoelectron spectrum of BCN thin films prepared in Comparative Example 1 (upper figure) and Example 1 (lower figure). DETAILED DESCRIPTION
[0034] The present invention provides a method for preparing a BCN thin film, comprising the following steps:
[0035] Mixing niobium hydroxide precipitate, a composite chelating agent and water, and dissolving them to obtain a precursor solution; the composite chelating agent includes ethylenediaminetetraacetic acid and tartaric acid;
[0036] adding a bismuth ion solution and a calcium ion solution dropwise to the precursor solution, and sequentially performing hydrolysis condensation reaction and aging to obtain a BCN gel;
[0037] The BCN gel is coated on the surface of a substrate and sintered to obtain the BCN film.
[0038] In the present invention, unless otherwise specified, all raw material components are commercially available products well known to those skilled in the art.
[0039] The present invention mixes niobium hydroxide precipitate, a composite chelating agent and water, and dissolves them to obtain a precursor solution.
[0040] In the present invention, the method for preparing the niobium hydroxide precipitate comprises the following steps:
[0041] mixing niobium pentoxide and hydrofluoric acid and performing double decomposition reaction to obtain a niobium fluoride solution;
[0042] The niobium fluoride solution and the ammonium ion solution are mixed, and precipitation reaction and solid-liquid separation are carried out in sequence to obtain the niobium hydroxide precipitate.
[0043] In the present invention, the hydrofluoric acid is analytically pure. In a specific embodiment, the concentration of the hydrofluoric acid can be 48 wt %. The molar ratio of the niobium pentoxide to the hydrogen fluoride in the hydrofluoric acid is 1:10-15, and in a specific embodiment, it can be 1:12. The temperature of the double decomposition reaction is 150-180° C., and in a specific embodiment, it can be 160° C. The reaction time is 2-3 h, and in a specific embodiment, it is 2-2.5 h.
[0044] In the present invention, the ammonium ion solution includes ammonium bicarbonate solution and / or ammonia water; the ammonium bicarbonate solution is a saturated ammonium bicarbonate solution; the mass concentration of the ammonia water is 25-28%; the molar ratio of ammonium bicarbonate in the ammonium bicarbonate solution to ammonia monohydrate in the ammonia water is 1:4-7, and in a specific embodiment, it can be 1:5-6; the pH value of the system after the niobium fluoride solution and the ammonium ion solution are mixed is 8-10, and in a specific embodiment, it can be 8-9; the temperature of the precipitation reaction is room temperature; the reaction time is 10-20 minutes, and in a specific embodiment, it can be 10-15 minutes; and the solid-liquid separation is centrifugation.
[0045] In the present invention, the composite chelating agent includes ethylenediaminetetraacetic acid (EDTA) and tartaric acid (TA); the molar ratio of tartaric acid to EDTA is 1:1-3, and in a specific embodiment, it can be 1:2; the molar ratio of the niobium hydroxide precipitate to the composite chelating agent is 1:6-8, and in a specific embodiment, it can be 1:7.
[0046] In the present invention, the mixing order is: first dissolving the complex chelating agent in water to obtain a complex chelating agent solution, and then adding the niobium hydroxide precipitate to the complex chelating agent solution; the concentration of the complex chelating agent in the complex chelating agent solution is 0.1 to 3 mol / L, and in a specific embodiment, can be 0.5 to 2.5 mol / L.
[0047] In the present invention, the dissolution temperature is 70-80° C. In the present invention, the amount of the chelating agent is limited according to the composition of the sol and the required film properties, and the chelating agent is fully mixed and reacted with the metal ions in the sol to ensure the formation of a stable sol system.
[0048] After obtaining the precursor solution, the present invention drips a bismuth ion solution and a calcium ion solution into the precursor solution, and sequentially performs hydrolysis condensation reaction and aging to obtain a BCN gel.
[0049] In the present invention, the preparation method of the bismuth ion solution includes: mixing a bismuth salt and water or an acid to obtain the bismuth ion solution; the bismuth salt includes one or more of bismuth chloride, bismuth oxychloride, bismuth nitrate, bismuth perchlorate, bismuth acetate, bismuth sulfate and bismuth carbonate; the acid includes hydrochloric acid and / or sulfuric acid; the hydrochloric acid is analytically pure, and in a specific embodiment, the concentration of the hydrochloric acid can be 37wt%; the molar ratio of the bismuth salt to the hydrogen chloride in the hydrochloric acid is 1:1.2-1.5, and in a specific embodiment, it can be 1:1.3.
[0050] In the present invention, the preparation method of the calcium ion solution includes: mixing a calcium salt and water or an acid to obtain the calcium ion solution; the calcium salt includes one or more of calcium chloride, calcium nitrate, calcium bicarbonate, calcium bisulfate, calcium dihydrogen phosphate and calcium hypochlorite; the acid includes hydrochloric acid; the concentration of the hydrochloric acid is; the molar ratio of the calcium salt to the hydrogen chloride in the hydrochloric acid is 1:1.2 to 1.5, and in a specific embodiment, it can be 1:1.3.
[0051] In the present invention, the molar ratio of bismuth ions in the bismuth ion solution to niobium ions in the precursor solution is 1:0.9-1.2, and in a specific embodiment, it can be 1:1; the molar ratio of calcium ions in the calcium ion solution to niobium ions in the precursor solution is 1:1.9-2.2, and in a specific embodiment, it can be 1:2.
[0052] In the present invention, the order of dropwise addition is bismuth ion solution and calcium ion solution; the dropwise addition rate of the bismuth ion solution and calcium ion solution is independently less than 3 mL / min, and in a specific embodiment, it can be 2 mL / min; the dropwise addition is carried out at 60-80°C, and in a specific embodiment, it can be 70°C; the dropwise addition is carried out under stirring; and after the dropwise addition, the solution is adjusted to a clear state with ammonia water, and the clarification ensures the stability of the precursor solution and is only a neutralization reaction. In the present invention, the purpose of limiting the dropwise addition order and dropwise addition rate is to ensure that the bismuth ions and calcium ions can react evenly with the niobium ions in the precursor solution, thereby promoting the smooth progress of the hydrolysis and condensation reaction, avoiding excessive reaction or local oversaturation, resulting in uneven precipitation or the formation of unstable intermediates. In addition, controlling the dropwise addition rate can help accurately control the reaction process and ensure the quality and stability of the final gel. The purpose of adjusting the pH value in the present invention is to regulate the degree of complexation between the metal ions and the chelating agent in the solution to avoid excessive hydrolysis or incomplete reaction, which in turn affects the formation and performance of the BCN gel. By adjusting the pH value to a clear solution, it is possible to ensure that the metal ions in the precursor solution are moderately hydrolyzed, promote a stable gelation process, ensure that the structure and performance of the final product meet the requirements, and prevent the substrate from being corroded.
[0053] In the present invention, the hydrolysis and condensation reaction further includes adding a stabilizer to the precursor solution before the hydrolysis and condensation reaction; the stabilizer includes ethylene glycol; the volume ratio of the stabilizer to the precursor solution is 1:2 to 5, and in a specific embodiment, it can be 1:3 to 4; the addition of the stabilizer is carried out at 60 to 80°C, and in a specific embodiment, it can be 70°C; the addition of the stabilizer is carried out under stirring. The role of adding a stabilizer in the present invention is to improve the stability of the sol. The sol is a suspension system in which nanoparticles are dispersed in a liquid phase. Over time, the nanoparticles may aggregate and settle, causing the sol to lose stability. The stabilizer can coat the surface of the particles through electrostatic or steric hindrance, prevent aggregation between particles, and maintain a stable dispersion state of the sol.
[0054] In the present invention, the temperature of the hydrolysis condensation reaction is 60-80°C, and in a specific embodiment, it can be 70°C; the reaction time is 1-3 hours, and in a specific embodiment, it can be 1-2 hours; the temperature of the aging is room temperature; the time is 20-24 hours, and in a specific embodiment, it can be 24 hours. The role of aging in the present invention is to improve the purity of the film. Aging is simply the formation of a gel from the sol to form a more uniform and dense three-dimensional network structure. "Aging" in the sol-gel method refers to the process of letting the system stand for a period of time after the sol is formed, so that further chemical reactions, physical structure reorganization and gradual coagulation occur inside the system, and finally forming a uniform and stable gel or improving the quality of the gel.
[0055] The reasons why composite chelating agents improve purity are: (1) they can effectively complex and improve the uniformity of the precursor. Composite chelating agents (such as tartaric acid and ethylenediaminetetraacetic acid) can form more stable complexes with metal ions (such as bismuth, calcium, and niobium). This stable complexation is conducive to the uniform dispersion of metal ions, reducing local concentration unevenness or premature precipitation, effectively controlling the material distribution during the reaction process, and improving the quality of the gel. (2) reducing the generation of oxygen vacancies. The generation of oxygen vacancies is mainly related to factors such as uneven composition in the precursor, non-uniform hydrolysis and condensation during the reaction, and incomplete redox during sintering. Composite chelating agents reduce these uneven factors through better complexing ability, thereby increasing the proportion of lattice oxygen in the BCN film and significantly reducing oxygen vacancies, thereby improving the purity of the film. (3) optimizing reaction kinetics. The synergistic effect of composite chelating agents can regulate the release rate of metal ions, making the hydrolysis and condensation reaction more controllable, avoiding the situation where the reaction rate is too fast or locally incomplete due to a single chelating agent, thereby reducing the formation of impurity phases and increasing the proportion of lattice oxygen. (4) Reduce defects and improve structural integrity. The composite chelating agent can reduce oxygen vacancies in BCN films, making the lattice structure more complete and reducing the defect concentration, which helps to improve the performance and purity of BCN films.
[0056] After obtaining the BCN gel, the present invention applies the BCN gel on the surface of a substrate and sintering the gel to obtain the BCN film.
[0057] In the present invention, the substrate comprises indium tin oxide (ITO) glass or fluorine-doped tin oxide (FTO) glass; the coating process includes cleaning the substrate prior to coating; the cleaning is ultrasonic cleaning, which includes sequentially washing with water, washing with acetone, washing with anhydrous ethanol, and washing with water; each ultrasonic cleaning lasts for 10 minutes; and the coating apparatus is a vacuum spin coater. By studying the growth of thin films on various substrates, the present invention uses FTO glass as the most suitable substrate material, facilitating the production of superior thin films and further improving their performance. The present invention also pre-treats the substrate to remove surface impurities and defects, thereby enhancing the bonding strength between the substrate and the film.
[0058] In the present invention, the sintering process also includes drying before sintering; the drying temperature is 110-130°C, and in specific embodiments, it can be 120°C, and the drying time is 10-20 minutes, and in specific embodiments, it can be 10 minutes; the sintering temperature is 650-750°C, and in specific embodiments, it can be 700°C, and the time is 2-3 hours, and in specific embodiments, it can be 2 hours. In the present invention, limiting the sintering process to the above range can optimize the crystal structure of the film.
[0059] In the present invention, the coating and sintering are performed 3 to 7 times, and in a specific embodiment, can be 5 or 6 times; the present invention has no special limitation on the coating amount, and after the above-mentioned number of coating and sintering, the thickness of the obtained BCN film can reach 300 to 450 nm.
[0060] The present invention prepares BCN thin films through a sol-gel method. Compared with other preparation methods, the sol-gel method has a simple preparation process, can make the composition of the film more uniform, and can produce high-purity films at a lower cost. At the same time, compared with the single chelating agent often used in traditional film preparation, the use of a composite chelating agent can form a more stable and complex complex with the metal ions in the sol, which is more conducive to the preparation of a stable sol, reduces film defects, and the resulting film has better performance. The preparation method of the present invention can significantly improve the stability of the sol, optimize the growth conditions of the film, and use the most suitable substrate material to prepare a more uniform film. These improvements not only improve the quality and reliability of the film, but also broaden the application field and market prospects of the film.
[0061] The present invention also provides a BCN film prepared by the preparation method described in the above technical solution.
[0062] As an embodiment, the oxygen vacancy ratio in the BCN film is 12.72%.
[0063] In order to further illustrate the present invention, the preparation method of the BCN thin film provided by the present invention is described in detail below with reference to the accompanying drawings and examples, but they should not be construed as limiting the scope of protection of the present invention.
[0064] The flow chart of the preparation method of the BCN film described in Examples 1 to 6 of the present invention is shown in FIG. Figure 1 The specific steps are as described in Examples 1 to 6.
[0065] Example 1
[0066] High-purity (99.99%) Nb2O5 was weighed and placed in a reactor with hydrofluoric acid (48 wt%) at a molar ratio of 1:10. A double decomposition reaction was carried out at 160°C for 2 hours to obtain a NbF5 solution. Saturated ammonium bicarbonate was mixed with 25 wt% ammonia water at a molar ratio of 1:5. The resulting mixture was added to the NbF5 solution, and the pH was adjusted to 8. The mixture was allowed to precipitate at room temperature for 10 minutes. After centrifugation, the resulting solid was washed twice with distilled water to obtain a Nb(OH)5 precipitate.
[0067] EDTA and TA were dissolved in deionized water at a molar ratio of 2:1 to prepare a composite chelating agent solution. The concentration of the chelating agent in the obtained composite chelating agent was 2.5 mol / L. Nb(OH)5 precipitate was added to the composite chelating agent solution.5+ The molar ratio of the compound to the complex chelating agent is 1:6, and the mixture is heated in a water bath at 80° C. with stirring until the precipitate is dissolved to obtain a Nb-TA-EDTA precursor solution.
[0068] High purity (99.99%) BiCl3 was dissolved in 37wt% hydrochloric acid with a molar ratio of BiCl3 to HCl of 1:1.2 to obtain Bi 3 + The concentration of bismuth ion solution is 2 mol / L. High purity (99.99%) CaCl2 is dissolved in 37wt% hydrochloric acid, and the molar ratio of CaCl2 to HCl is 1:1.2 to obtain Ca 2+ Calcium ion solution with a concentration of 1 mol / L.
[0069] The bismuth ion solution and calcium ion solution were sequentially added dropwise to the Nb-TA-EDTA precursor solution at a rate of 2 mL / min. 2 + 、Bi 3+ and Nb 5+ The mixture was stirred in a water bath at 70°C for the entire process. After the addition was complete, the solution was adjusted to clarity with aqueous ammonia. 15 mL of ethylene glycol was then added, with a volume ratio of ethylene glycol to the precursor solution of 1:4. The mixture was heated and stirred for 1 hour, and then sealed and aged at room temperature for 24 hours to obtain a BCN gel.
[0070] The FTO glass substrate was ultrasonically cleaned in deionized water, acetone, anhydrous ethanol, and deionized water for 10 minutes each to remove surface impurities. The BCN gel was then coated onto the pretreated FTO substrate using a vacuum spin coater. After drying on a hotplate at 110°C for 10 minutes, the gel was sintered in a tube furnace at 650°C for 2 hours to form a BCN film. This process was repeated five times to obtain a BCN film with a cubic pyrochlore structure and a thickness of 300 to 450 nm.
[0071] Example 2
[0072] High-purity (99.99%) Nb2O5 was weighed and placed in a reactor with hydrofluoric acid (48 wt%) at a molar ratio of 1:10. A double decomposition reaction was carried out at 160°C for 2 hours to obtain a NbF5 solution. Saturated ammonium bicarbonate was mixed with 25 wt% ammonia water at a molar ratio of 1:5. The resulting mixture was added to the NbF5 solution, and the pH was adjusted to 8. The mixture was allowed to precipitate at room temperature for 10 minutes. After centrifugation, the resulting solid was washed twice with distilled water to obtain a Nb(OH)5 precipitate.
[0073] EDTA and TA were dissolved in deionized water at a molar ratio of 2:1 to prepare a composite chelating agent solution. The concentration of the chelating agent in the obtained composite chelating agent was 2.5 mol / L. Nb(OH)5 precipitate was added to the composite chelating agent solution. 5+ The molar ratio of the compound to the complex chelating agent is 1:6, and the mixture is heated in a water bath at 80° C. with stirring until the precipitate is dissolved to obtain a Nb-TA-EDTA precursor solution.
[0074] High purity (99.99%) BiCl3 was dissolved in 37wt% hydrochloric acid with a molar ratio of BiCl3 to HCl of 1:1.2 to obtain Bi 3 + The concentration of bismuth ion solution is 2 mol / L. High purity (99.99%) CaCl2 is dissolved in 37wt% hydrochloric acid, and the molar ratio of CaCl2 to HCl is 1:1.2 to obtain Ca 2+ Calcium ion solution with a concentration of 1 mol / L.
[0075] The bismuth ion solution and calcium ion solution were sequentially added dropwise to the Nb-TA-EDTA precursor solution at a rate of 2 mL / min. 2 + 、Bi 3+ and Nb 5+ The mixture was stirred in a water bath at 70°C for the entire process. After the addition was complete, the solution was adjusted to clarity with aqueous ammonia. 15 mL of ethylene glycol was then added, with a volume ratio of ethylene glycol to the precursor solution of 1:4. The mixture was heated and stirred for 1 hour, and then sealed and aged at room temperature for 24 hours to obtain a BCN gel.
[0076] The FTO glass substrate was ultrasonically cleaned in deionized water, acetone, anhydrous ethanol, and deionized water for 10 minutes each to remove surface impurities. The BCN gel was then coated onto the pretreated FTO substrate using a vacuum spin coater. After drying on a hotplate at 110°C for 10 minutes, the gel was sintered in a tube furnace at 700°C for 2 hours to form a BCN film. This process was repeated five times to obtain a BCN film with a cubic pyrochlore structure and a thickness of 300 to 450 nm.
[0077] Example 3
[0078] High-purity (99.99%) Nb2O5 was weighed and placed in a reactor with hydrofluoric acid (48 wt%) at a molar ratio of 1:10. A double decomposition reaction was carried out at 160°C for 2 hours to obtain a NbF5 solution. Saturated ammonium bicarbonate was mixed with 25 wt% ammonia water at a molar ratio of 1:5. The resulting mixture was added to the NbF5 solution, and the pH was adjusted to 8. The mixture was allowed to precipitate at room temperature for 10 minutes. After centrifugation, the resulting solid was washed twice with distilled water to obtain a Nb(OH)5 precipitate.
[0079] EDTA and TA were dissolved in deionized water at a molar ratio of 2:1 to prepare a composite chelating agent solution. The concentration of the chelating agent in the obtained composite chelating agent was 2.5 mol / L. Nb(OH)5 precipitate was added to the composite chelating agent solution. 5+ The molar ratio of the compound to the complex chelating agent is 1:6, and the mixture is heated in a water bath at 80° C. with stirring until the precipitate is dissolved to obtain a Nb-TA-EDTA precursor solution.
[0080] High purity (99.99%) BiCl3 was dissolved in 37wt% hydrochloric acid with a molar ratio of BiCl3 to HCl of 1:1.2 to obtain Bi 3 + The concentration of bismuth ion solution is 2 mol / L. High purity (99.99%) CaCl2 is dissolved in 37wt% hydrochloric acid, and the molar ratio of CaCl2 to HCl is 1:1.2 to obtain Ca 2+ Calcium ion solution with a concentration of 1 mol / L.
[0081] The bismuth ion solution and calcium ion solution were sequentially added dropwise to the Nb-TA-EDTA precursor solution at a rate of 2 mL / min. 2 + 、Bi 3+ and Nb 5+ The mixture was stirred in a water bath at 70°C for the entire process. After the addition was complete, the solution was adjusted to clarity with aqueous ammonia. 15 mL of ethylene glycol was then added, with a volume ratio of ethylene glycol to the precursor solution of 1:4. The mixture was heated and stirred for 1 hour, and then sealed and aged at room temperature for 24 hours to obtain a BCN gel.
[0082] The FTO glass substrate was ultrasonically cleaned in deionized water, acetone, anhydrous ethanol, and deionized water for 10 minutes each to remove surface impurities. The BCN gel was then coated onto the pretreated FTO substrate using a vacuum spin coater. After drying on a hotplate at 110°C for 10 minutes, the gel was sintered in a tube furnace at 750°C for 2 hours to form a BCN film. This process was repeated five times to obtain a BCN film with a cubic pyrochlore structure and a thickness of 300 to 450 nm.
[0083] Example 4
[0084] High-purity (99.99%) Nb2O5 was weighed and placed in a reactor with hydrofluoric acid (48 wt%) at a molar ratio of 1:10. A double decomposition reaction was carried out at 160°C for 2 hours to obtain a NbF5 solution. Saturated ammonium bicarbonate was mixed with 25 wt% ammonia water at a molar ratio of 1:5. The resulting mixture was added to the NbF5 solution, and the pH was adjusted to 8. The mixture was allowed to precipitate at room temperature for 10 minutes. After centrifugation, the resulting solid was washed twice with distilled water to obtain a Nb(OH)5 precipitate.
[0085] EDTA and TA were dissolved in deionized water at a molar ratio of 2:1 to prepare a composite chelating agent solution. The concentration of the chelating agent in the obtained composite chelating agent was 2.5 mol / L. Nb(OH)5 precipitate was added to the composite chelating agent solution. 5+ The molar ratio of the compound to the complex chelating agent is 1:6, and the mixture is heated in a water bath at 80° C. with stirring until the precipitate is dissolved to obtain a Nb-TA-EDTA precursor solution.
[0086] High purity (99.99%) BiCl3 was dissolved in 37wt% hydrochloric acid with a molar ratio of BiCl3 to HCl of 1:1.2 to obtain Bi 3 + The concentration of bismuth ion solution is 2 mol / L. High purity (99.99%) CaCl2 is dissolved in 37wt% hydrochloric acid, and the molar ratio of CaCl2 to HCl is 1:1.2 to obtain Ca 2+ Calcium ion solution with a concentration of 1 mol / L.
[0087] The bismuth ion solution and calcium ion solution were sequentially added dropwise to the Nb-TA-EDTA precursor solution at a rate of 2 mL / min. 2 + 、Bi 3+ and Nb 5+ The mixture was stirred in a water bath at 70°C for the entire process. After the addition was complete, the solution was adjusted to clarity with aqueous ammonia. 15 mL of ethylene glycol was then added, with a volume ratio of ethylene glycol to the precursor solution of 1:4. The mixture was heated and stirred for 1 hour, and then sealed and aged at room temperature for 24 hours to obtain a BCN gel.
[0088] The ITO glass substrate was ultrasonically cleaned in deionized water, acetone, anhydrous ethanol, and deionized water for 10 minutes each to remove surface impurities. The BCN gel was then coated onto the pretreated ITO substrate using a vacuum spin coater. After drying on a hotplate at 110°C for 10 minutes, the gel was sintered in a tube furnace at 650°C for 2 hours to form a BCN film. This process was repeated five times to obtain a BCN film with a cubic pyrochlore structure and a thickness of 300 to 450 nm.
[0089] Example 5
[0090] High-purity (99.99%) Nb2O5 was weighed and placed in a reactor with hydrofluoric acid (48 wt%) at a molar ratio of 1:12. A double decomposition reaction was carried out at 150°C for 2 hours to obtain a NbF5 solution. Saturated ammonium bicarbonate was mixed with 25 wt% ammonia water at a molar ratio of 1:5. The resulting mixture was added to the NbF5 solution, and the pH was adjusted to 8. The mixture was allowed to precipitate at room temperature for 10 minutes. After centrifugation, the resulting solid was washed twice with distilled water to obtain a Nb(OH)5 precipitate.
[0091] EDTA and TA were dissolved in deionized water at a molar ratio of 2:1 to prepare a composite chelating agent solution. The concentration of the chelating agent in the obtained composite chelating agent was 2.5 mol / L. Nb(OH)5 precipitate was added to the composite chelating agent solution. 5+ The molar ratio of the compound to the complex chelating agent is 1:6, and the mixture is heated in a water bath at 80° C. with stirring until the precipitate is dissolved to obtain a Nb-TA-EDTA precursor solution.
[0092] High purity (99.99%) BiCl3 was dissolved in 37wt% hydrochloric acid with a molar ratio of BiCl3 to HCl of 1:1.3 to obtain Bi 3 + The concentration of bismuth ion solution is 2 mol / L. High purity (99.99%) CaCl2 is dissolved in 37wt% hydrochloric acid, and the molar ratio of CaCl2 to HCl is 1:1.3 to obtain Ca 2+ Calcium ion solution with a concentration of 1 mol / L.
[0093] The bismuth ion solution and calcium ion solution were sequentially added dropwise to the Nb-TA-EDTA precursor solution at a rate of 2 mL / min. 2 + 、Bi 3+ and Nb 5+ The mixture was stirred in a water bath at 75°C for the entire process. After the addition was complete, the solution was adjusted to clarity with aqueous ammonia. 15 mL of ethylene glycol was then added, with a volume ratio of ethylene glycol to the precursor solution of 1:4. The mixture was heated and stirred for 2 hours, and then sealed and aged at room temperature for 24 hours to obtain a BCN gel.
[0094] The ITO glass substrate was ultrasonically cleaned in deionized water, acetone, anhydrous ethanol, and deionized water for 10 minutes each to remove surface impurities. The BCN gel was then coated onto the pretreated ITO substrate using a vacuum spin coater. After drying on a hotplate at 120°C for 10 minutes, the gel was sintered in a tube furnace at 700°C for 2 hours to form a BCN film. This process was repeated six times to obtain a BCN film with a cubic pyrochlore structure and a thickness of 300 to 450 nm.
[0095] Example 6
[0096] High-purity (99.99%) Nb2O5 was weighed and placed in a reactor with hydrofluoric acid (48 wt%) at a molar ratio of 1:15. A double decomposition reaction was carried out at 150°C for 2 hours to obtain a NbF5 solution. Saturated ammonium bicarbonate was mixed with 25 wt% aqueous ammonia at a molar ratio of 1:4. The resulting mixture was added to the NbF5 solution, and the pH was adjusted to 8. The mixture was allowed to precipitate at room temperature for 10 minutes. After centrifugation, the resulting solid was washed twice with distilled water to obtain a Nb(OH)5 precipitate.
[0097] EDTA and TA were dissolved in deionized water at a molar ratio of 2:1 to prepare a composite chelating agent solution. The concentration of the chelating agent in the obtained composite chelating agent was 2.5 mol / L. Nb(OH)5 precipitate was added to the composite chelating agent solution. 5+ The molar ratio of the compound to the complex chelating agent is 1:6, and the mixture is heated in a water bath at 80° C. with stirring until the precipitate is dissolved to obtain a Nb-TA-EDTA precursor solution.
[0098] High purity (99.99%) BiCl3 was dissolved in 37wt% hydrochloric acid with a molar ratio of BiCl3 to HCl of 1:1.5 to obtain Bi 3 + The concentration of bismuth ion solution is 2 mol / L. High purity (99.99%) CaCl2 is dissolved in 37wt% hydrochloric acid, and the molar ratio of CaCl2 to HCl is 1:1.5 to obtain Ca 2+ Calcium ion solution with a concentration of 1 mol / L.
[0099] The bismuth ion solution and calcium ion solution were sequentially added dropwise to the Nb-TA-EDTA precursor solution at a rate of 2 mL / min. 2 + 、Bi 3+ and Nb 5+ The mixture was stirred in a water bath at 75°C for the entire process. After the addition was complete, the solution was adjusted to clarity with aqueous ammonia. 15 mL of ethylene glycol was then added, with a volume ratio of ethylene glycol to the precursor solution of 1:4. The mixture was heated and stirred for 2 hours, and then sealed and aged at room temperature for 24 hours to obtain a BCN gel.
[0100] An ITO glass substrate was ultrasonically cleaned in deionized water, acetone, anhydrous ethanol, and deionized water for 10 minutes each to remove surface impurities. A BCN gel was then coated onto the pretreated ITO substrate using a vacuum spin coater. After drying on a hotplate at 130°C for 10 minutes, the gel was sintered in a tube furnace at 750°C for 2 hours to form a BCN film. This process was repeated six times to obtain a BCN film with a cubic pyrochlore structure and a thickness of 300 to 450 nm.
[0101] Comparative Example 1
[0102] The difference from Example 1 is that the composite chelating agent (EDTA and TA) is replaced by an equal amount of a single chelating agent (EDTA). The rest of the contents are the same as those in Example 1, and a BCN film is prepared.
[0103] Test Case
[0104] The BCN films prepared in Examples 1 to 6 were subjected to X-ray diffraction tests using an X-ray diffractometer and morphology analysis using a scanning electron microscope. The XRD patterns of the BCN films obtained in Examples 1 to 3 are shown in FIG. Figure 2 The XRD patterns of the BCN films obtained in Examples 4 to 6 are shown in Figure 3 The SEM images of the BCN films obtained in Examples 1 to 6 are shown in FIG. Figure 4 , wherein Figures a to f correspond to Examples 1 to 6 respectively, Figure 5 Peak analysis diagram of O1s XPS photoelectron spectrum of BCN thin films prepared in Comparative Example 1 (upper figure) and Example 1 (lower figure).
[0105] Depend on Figures 2-3 As can be seen, the X-ray diffraction patterns of BCN films grown on both ITO and FTO substrates exhibit different characteristics as the sintering temperature changes. However, apart from the peaks of the substrate, only the BCN peaks are present, with no other phases. All phases are orthorhombic CaBi2Nb2O9 and are of high purity.
[0106] The XRD pattern shows significant changes in both the intensity and position of the diffraction pattern fringes as the temperature decreases from 750°C to 650°C. This may be due to adjustments in the film's crystal structure during the cooling process, or may involve processes such as lattice contraction, phase transitions, or defect formation.
[0107] Combine Figure 4 From the above, it can be seen that the grain size of the film grown on the ITO substrate is larger than that of the film grown on the FTO substrate. The grain size of the film grown on the FTO substrate, especially the film grown at 700°C, is more uniform and dense. Therefore, the more optimal experimental conditions in the embodiments provided by the present invention are 700°C and FTO substrate.
[0108] Figure 5 The proportion of lattice oxygen (Lattice Oxygen) and oxygen vacancy (Oxygen Vacancy) in the two BCN samples prepared in Comparative Example 1 and Example 1 is shown. Figure 5 It can be seen that the lattice oxygen ratio of the BCN film prepared in Comparative Example 1 using a single chelating agent is 76.63%, and the oxygen vacancy ratio is 23.37%. In contrast, the lattice oxygen ratio of the BCN film prepared in Example 1 using a composite chelating agent is 87.28%, and the oxygen vacancy ratio is reduced to 12.72%. The reduction of the oxygen vacancy ratio to 12.72% in the BCN film using the composite chelating agent indicates that the lattice structure of the BCN film is more complete and the defect concentration is reduced, which helps to improve the film performance and purity.
[0109] Although the above embodiment provides a detailed description of the present invention, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the scope of protection of the present invention.
Claims
1. A method for preparing a BCN thin film, characterized in that: The following steps are involved: Mixing niobium hydroxide precipitate, a composite chelating agent and water, dissolving them, and obtaining a precursor solution; the composite chelating agent comprises ethylenediaminetetraacetic acid and tartaric acid; Adding a bismuth ion solution and a calcium ion solution dropwise into the precursor solution, and sequentially performing a hydrolysis condensation reaction and aging to obtain a BCN gel; The BCN gel is coated on the surface of a substrate and sintered to obtain the BCN film.
2. The preparation method according to claim 1, characterized in that: The molar ratio of tartaric acid to ethylenediaminetetraacetic acid is 1:1-3; The molar ratio of the niobium hydroxide precipitate to the composite chelating agent is 1:6-8.
3. The preparation method according to claim 1 or 2, characterized in that: The dissolving temperature is 70-80°C.
4. The preparation method according to claim 1, characterized in that: The molar ratio of the bismuth ions in the bismuth ion solution to the niobium ions in the precursor solution is 1:0.9-1.2; The molar ratio of calcium ions in the calcium ion solution to niobium ions in the precursor solution is 1:1.9-2.
2.
5. The preparation method according to claim 1, characterized in that: The method further comprises adding a stabilizer into the precursor solution before the hydrolysis condensation reaction; the stabilizer comprises ethylene glycol.
6. The preparation method according to claim 1, 4 or 5, characterized in that: The dropping rates of the bismuth ion solution and the calcium ion solution are independently below 3 mL / min; The temperature of the hydrolysis condensation reaction is 60-80°C, and the reaction time is 1-3h; The aging temperature is room temperature and the aging time is 20 to 24 hours.
7. The preparation method according to claim 1, characterized in that: The substrate comprises indium tin oxide glass or fluorine-doped tin oxide glass; The sintering temperature is 650-750° C. and the sintering time is 2-3 hours.
8. The preparation method according to claim 1, characterized in that: The method for preparing the niobium hydroxide precipitate comprises the following steps: Mixing niobium pentoxide and hydrofluoric acid to perform double decomposition reaction to obtain a niobium fluoride solution; The niobium fluoride solution and the ammonium ion solution are mixed, and precipitation reaction and solid-liquid separation are carried out in sequence to obtain the niobium hydroxide precipitate.
9. The preparation method according to claim 8, characterized in that: The molar ratio of the niobium pentoxide to the hydrogen fluoride in the hydrofluoric acid is 1:10-15; The temperature of the double decomposition reaction is 150-180° C., and the reaction time is 2-3 hours.
10. The BCN thin film prepared by the preparation method according to any one of claims 1 to 9.